The Influence of Social Commerce and Influencers on Purchase Intention at TikTokShop in Cirebon City - Elok Faiko; Annisa Fitri; Lis Tatin Hernidatiatin (Jurnal Manajemen (Edisi Elektronik), 2025)
Currently, the TikTok app has become one of the most popular platforms in Indonesia, prompting business players to innovate in offering products through the TikTok Shop platform in order to increase consumer purchase intentions. This study aims to analyze the influence of Social Commerce and Influencers on purchase intentions at TikTok Shop in Cirebon City. This research uses a quantitative method with a Likert scale as the measurement tool. The population in this study is the people of Cirebon City who have the TikTok app. For the sampling technique, the researcher used a nonprobability sampling method. Meanwhile, the sampling technique used is incidental sampling. The data were processed using the IBM SPSS Statistics application. The results of the study show that, partially, Social Commerce has a positive and significant effect on purchase intentions at TikTok Shop. Similarly, the Influencer variable also has a positive and significant effect on purchase intentions at TikTok Shop. Simultaneously, Social Commerce and Influencers have a positive and significant effect on purchase intentions at TikTok Shop in Cirebon City. Therefore, this study emphasizes that Social Commerce and Influencers play an important role in increasing consumer purchase intentions at TikTok Shop.